Desarrollo de estrategias de educación ambiental para mejorar la calidad ambiental en el CETMAR 08 - Romero-Osuna, Alexis Guadalupe; Ramírez-López, Jesús Antonio (Ra ximhai, 2023)
Different strategies of environmental education applied in the CETMAR 08 in the last year are presented with the purpose of improving the environmental quality of the campus, for which transversal activities were carried out in the subjects of ecology and geometry and trigonometry, as well as with the different specialties. The planning of the activities was carried out taking into account a diagnosis made by the participating teachers, as well as the national and international environmental festivities and the environmental problems detected by the students in the school and the nearby environment (Estero de Urías). A good response was obtained from the students and teachers participating in the different activities, which served to promote reflection and awareness about the care and improvement of the school environment.